(untitled) (Cardiovascular Journal, 2015)
The management of combined Coronary Artery Disease and Peripheral Vascular Disease is a challenge and brings with it numerous clinical dilemmas. The 56 year old gentleman presented to our department with significant triple vessel disease with occluded lower end of aorta just before bifurcation and occluded bilateral superficial femoral arteries. CABG with aorto-femoral and femoro popliteal bypass was done on the same setting. On 12th postoperative day he was discharged from hospital in good general condition. Follow up after 6 months of operation the patient is doing well and free of chest pain and claudication pain. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22266 Cardiovasc. j. 2015; 7(2): 159-161